Chronic Illness and Fatigue in Older Individuals: A Systematic Review. Issue 3 (May 2021) - Torossian, Maral; Jacelon, Cynthia S.
Abstract: Background: Fatigue is a symptom experienced by 40%–74% of older individuals in the United States. Despite its significance, clinicians face challenges helping individuals to manage or reduce fatigue levels. Some management issues are attributable to the ambiguity around the risk factors, consequences, and the effect of fatigue management strategies. Methods: A literature review was conducted using four databases to identify themes in relation to risk factors, consequences, and management strategies from research studies about fatigue in older individuals with chronic diseases. Results: Findings on fatigue risk factors, such as age, body mass index, and marital status, were contradictory. There was a positive association between fatigue and comorbidities, depression, and anxiety and a negative relationship between fatigue and physical activity, sleep, educational status, and socioeconomic status. Fatigue was perceived as a state of "feebleness" and negatively impacted individuals' quality of life. Consequences of fatigue included tiredness, sleepiness, depression, anxiety, worse sense of purpose in life, poor self-care, and an increased β-amyloid load. Predictors of worse fatigue consequences included functional health, symptom burden, subjective health, and self-acceptance. Fatigue management strategies included physical activity, rest, sleep, maintaining normal hemoglobin levels, and acetyl-L-carnitine supplementation. Conclusion: This systematic review is of value to older individuals with chronic illnesses, researchers, and clinicians who strive to improve the quality of life of individuals experiencing fatigue. To prevent undesirable consequences of fatigue, older individuals should be screened for the discussed modifiable risk factors of fatigue. The inconsistencies in the studies reviewed can guide researchers to potential research areas that require further inquiry and exploration to ground future practice on best scientific evidence